Optimization of the Samapta Patrol to Prevent the Crime of Serious Theft in the Jurisdiction of the Tegal Resort Police - I Wayan Widia Wijaya (Police Studies Review, 2022)
The rise of criminal acts of serious theft in Tegal Regency has become a problem and has caused unrest for the people of Tegal Regency. The National Police must prevent this through patrol activities by the Patrol Unit of the Tegal Police Samapta Unit. This research aims to identify the optimization of the Samapta patrol in preventing the crime of serious theft in the jurisdiction of the Tegal Police. This research was conducted in the jurisdiction of the Tegal Police, Central Java. This study uses a qualitative approach and field research methods. Data collection is done by conducting interviews, observations, and document studies. The data analysis techniques used are data collection, data reduction, data presentation, and concluding. This research uses conceptual literature including the optimization concept, theft concept by weighting, crime prevention concept, patrol concept, and management theory. The factual condition in this study is the crime of serious theft occurring at night with the mode of damaging doors, windows, and tiles. In the implementation of the samapta patrol to prevent the crime of theft, the emphasis is on the type of dialogical patrol. The optimization of patrols that have been carried out is using a dialogical strategy in making plans, carrying out joint patrols with the ranks of the police, adding personnel from other units, and using the GTMCC (Galawi Traffic Management Command Center) innovation, as well as a reward and punishment program. In practice, patrols are influenced by internal and external factors. Internal factors include the lack of number and quality of personnel, lack of fuel budget support and vehicle repairs, beat routes are always the same, and patrol targets that are not following the development of the crime of stealing. While external factors include coordination and cooperation with related functions and the community to support the implementation of patrols. The conclusion of this research is that the implementation of patrols by the Patrol Unit of the Tegal Police Samapta Unit to prevent the crime of serious theft isn’t optimal. Likewise, the optimization of the samapta patrol to prevent the crime of serious theft in the jurisdiction of the Tegal Resort Police hasn’t obtained optimal results.